2015
DOI: 10.1016/j.jhep.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

24-nor-ursodeoxycholic acid ameliorates inflammatory response and liver fibrosis in a murine model of hepatic schistosomiasis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Because immune cell-derived chemokines play a vital role in schistosome-induced pathology[25,26], one method to hamper disease progression could be by modulating chemokine production to limit hepatic eosinophil recruitment[27]. Importantly, although praziquantel therapy effectively kills adult Schistosoma , it has diminutive effects on liver fibrogenesis or portal hypertension[28,29]; thus, new strategies to treat schistosomiasis are urgently needed.…”
Section: Etiology and Pathological Characteristics Of Hepatic Fibrosismentioning
confidence: 99%
“…Because immune cell-derived chemokines play a vital role in schistosome-induced pathology[25,26], one method to hamper disease progression could be by modulating chemokine production to limit hepatic eosinophil recruitment[27]. Importantly, although praziquantel therapy effectively kills adult Schistosoma , it has diminutive effects on liver fibrogenesis or portal hypertension[28,29]; thus, new strategies to treat schistosomiasis are urgently needed.…”
Section: Etiology and Pathological Characteristics Of Hepatic Fibrosismentioning
confidence: 99%
“…Nor-UDCA has, in addition to its potent choleretic and cholangiocyte healing actions, 109 notable antifibrotic actions in mouse models of liver disease, 110 whilst FXR agonists also seem to be potently antifibrotic. 111 However, the apparent functional absence of FXR in human (as opposed to mouse) myofibroblasts argues against this mechanism of action in humans.…”
Section: Targeting Fibrosismentioning
confidence: 99%
“…commun., Vienna, January 2012], indicating that targeting fibrosis may be of key importance. Notably, a recent study demonstrated more general antifibrotic and immunomodulatory actions of nor UDCA (but again not UDCA) on granuloma size and hepatic fibrosis in a mouse model of Schistosoma mansoni infection, a leading cause of hepatic fibrosis and portal hypertension [22]. The anti-inflammatory properties of nor UDCA were directed to MHC class II protein expression on dendritic cells and macrophages and nor UDCA reduced T-lymphocyte proliferation and serum levels of profibrogenic Th2 cytokines IL-13 and IL-4 [22].…”
Section: Nor Udca For Cholestatic Liver Diseasesmentioning
confidence: 99%
“…Notably, a recent study demonstrated more general antifibrotic and immunomodulatory actions of nor UDCA (but again not UDCA) on granuloma size and hepatic fibrosis in a mouse model of Schistosoma mansoni infection, a leading cause of hepatic fibrosis and portal hypertension [22]. The anti-inflammatory properties of nor UDCA were directed to MHC class II protein expression on dendritic cells and macrophages and nor UDCA reduced T-lymphocyte proliferation and serum levels of profibrogenic Th2 cytokines IL-13 and IL-4 [22]. Apart from the relevance of these findings for the treatment of hepatic schistosomiasis as one of the worldwide leading causes of portal hypertension, such properties may also contribute to anti-inflammatory and antifibrotic effects of nor UDCA in other noncholestatic and cholestatic conditions.…”
Section: Nor Udca For Cholestatic Liver Diseasesmentioning
confidence: 99%